PENGARUH VULVA HYGIENE TERHADAP PENYEMBUHAN LUKA HEACTING ROBEKAN JALAN LAHIR PADA IBU BERSALIN - Desideria Yosepha Ginting; Agnes Erna Uly Saragih Simarmata; Layari Tarigan; Damayanti Damayanti (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Childbirth is a moment that has been eagerly awaited but not a few were found by women experiencing birth tears in the passenger, both in primigravida and multigravida. Improper perineal care can result in perineal conditions that are affected by lochea and moisture will greatly support the proliferation of bacteria that can cause infection in the perineum. The purpose of this study was to determine the effect of vulva hygiene on the healing of wound healing of rips in the birth canal of women in BPM Midwife A. Nagori P. Simalungun in 2019. This type of research is quasi-experimental designs with the study design is two group post-test design. This research was conducted at BPM Midwife A. Nagori P. Simalungun. The population in this study were all postpartum mothers who suffered torn passenger injuries at BPM Midwife A. Nagori P. Simalungun in May-June 2019 as many as 30 people. The sampling technique in this study is total sampling. Data was collected by using a checklist sheet and an observation sheet containing the results of the post-test of healing the wound healing of rips in the passenger in labor. Data analysis using the Spearman Rho test with an alpha value of 0.05.